Indonesian Adaptation and Psychometric Properties Evaluation of the Big Five Personality Inventory: IPIP-BFM-50 - Akhtar, Hanif; Azwar, Saifuddin (Faculty of Psychology, Universitas Gadjah Mada, 2019)
The big five personality traits are the best acknowledged and most commonly used the model in psychology. Therefore, many personality scales are developed based on this personality model. IPIP-BFM-50 is one of the open-source scales measuring big five personalities that is widely used by world researchers. This study aimed to adapt IPIP-BFM-50 into Indonesian and evaluate its psychometric properties. The adaptation was done by following the guidelines of the International Test Commission (ITC). The result shows that IPIP-BFM-50 Indonesia has Aiken's V index ranging from 0.71 - 0.98. Alpha reliability with n = 502 ranges from 0.762 (agreeableness) to 0.862 (emotional stability). Factor analysis shows that the items are well-grouped according to their dimensions with loading factor ranging from 0.34 to 0.75 on the factors measured. Thus, IPIP-BFM-50 Indonesia has satisfactory psychometric properties and can be used to measure the Big five personality.